2014
DOI: 10.1371/journal.pone.0114320
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Exclusion of TCR α-Chains upon Severe Restriction of Vα Repertoire

Abstract: Development of thymocytes through the positive selection checkpoint requires the rearrangement and expression of a suitable T cell receptor (TCR) α-chain that can pair with the already-expressed β-chain to make a TCR that is selectable. That is, it must have sufficient affinity for self MHC-peptide to induce the signals required for differentiation, but not too strong so as to induce cell death. Because both alleles of the α-chain continue to rearrange until a positively-selectable heterodimer is formed, thymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We observed that the proportion of Vα3.2 + CD8 + T cells and Vα3.2 + Vβ5.1/5.2 + cells was triple or more in the periphery of Themis –/– mice than Themis +/+ mice. We have previously found in rearranging TCR minigene mice that co-expression of Vα3.2 and Vβ5.2 is a favored combination ( 70 ). This increase in the number of CD8 + T cells carrying Vα3.2 TCR occurred in the periphery, as the proportion of these cells in the thymus were similar between Themis –/– and Themis +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the proportion of Vα3.2 + CD8 + T cells and Vα3.2 + Vβ5.1/5.2 + cells was triple or more in the periphery of Themis –/– mice than Themis +/+ mice. We have previously found in rearranging TCR minigene mice that co-expression of Vα3.2 and Vβ5.2 is a favored combination ( 70 ). This increase in the number of CD8 + T cells carrying Vα3.2 TCR occurred in the periphery, as the proportion of these cells in the thymus were similar between Themis –/– and Themis +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, allelic exclusion ensures that only one receptor may be expressed on the surface of the cell, but this process is leaky: 7% of T-cells have two productive β -chains [ 19 , 20 ], and %1 express both of them on the surface [ 21 – 23 ]. Allelic exclusion in the α chain is less well quantified as it relies on different mechanisms [ 24 , 25 ], with estimates ranging from 7% [ 8 ] to 30% [ 22 ] of cells with two functionally expressed α chains.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, allelic exclusion ensures that only one receptor may be expressed on the surface of the cell, but this process is leaky: 7% of T-cells have two productive β-chains [19,20], and %1 express both of them on the surface [21][22][23]. Allelic exclusion in the α chain is less well quantified as it relies on different mechanisms [24,25], with estimates ranging from 7% [8] to 30% [22] of cells with two functionally expressed α chains.…”
Section: Introductionmentioning
confidence: 99%